EP1297 SENTOV (SENtinel lymph node technique in OVarian cancer): video technique. (1st November 2019) - Lago, V; Bello, P; Padilla-Iserte, P; Matute, L; Marina, T; Gurrea, M; Domingo, S
Abstract : Introduction/Background: There is limited evidence favoring the use of the sentinel lymph node technique in ovarian cancer, and no standardized approach has been studied. The objective of the video is to show the standardized sentinel lymph node technique in early ovarian cancer Methodology: In the case of malignancy, the sentinel lymph node technique was performed. We subperitoneally injected 0.2 mL of saline solution containing 37 mBq of 99mTc nanocolloid (Albu-res, Pharmaceutical Nycomed Amersham, Braunschweig, Germany). At the same time, 0.5 mL of indocyanine green (concentration 1.25 mg/mL) was injected. We used a 27 G needle at each injection point Results: The sentinel lymph nodes were checked with an intra-operative mobile gamma camera (Sentinellatm, Oncovision) for descriptive purposes only. Thirty minutes after the injection, the SLN procedure was started regardless of probe migration with the IMGC. Guided by the acoustic signal of a gamma probe (Wprobe wireless gamma probe STD and LAP, Oncovision), we performed a minimum dissection looking for the hottest sentinel lymph node(s) in the pelvic/para-aortic region. We simultaneously used the Imagen1 HUB-OPAL1 (NIR/ICG system) (Karl Storz Endoscopy, GmbH, Mittelstrasse, Tuttlingen, Germany) to detect the sentinel lymph node(s) dyed with indocyanine green. Any lymph node with a remarkably higher count than the background was considered a sentinel lymph node and was harvested separately. Conclusion: In light of the findings of SENTOV clinical trial, the sentinel lymph node technique appears to be applicable in early-stage ovarian cancer Disclosure: Nothing to disclose